Prescriber Adoption of SLCO1B1 Genotype‐Guided Simvastatin Clinical Decision Support in a Clinical Pharmacogenetics Program. Issue 2 (17th November 2022) - Obeng, Aniwaa Owusu; Scott, Stuart A.; Kaszemacher, Tom; Ellis, Stephen B.; Mejia, Ana; Gomez, Alanna; Nadukuru, Rajiv; Abul‐Husn, Noura S.; Vega, Aida; Waite, Eva; Gottesman, Omri; Cho, Judy; et al.
Abstract : Pharmacogenetic implementation programs are increasingly feasible due to the availability of clinical guidelines for implementation research. The utilization of these resources has been reported with selected drug–gene pairs; however, little is known about how prescribers respond to pharmacogenetic recommendations for statin therapy. We prospectively assessed prescriber interaction with point‐of‐care clinical decision support (CDS) to guide simvastatin therapy for a diverse cohort of primary care patients enrolled in a clinical pharmacogenetics program. Of the 1, 639 preemptively genotyped patients, 298 (18.2%) had an intermediate function (IF) OATP1B1 phenotype and 25 (1.53%) had a poor function (PF) phenotype, predicted by a common single nucleotide variant in the SLCO1B1 gene (c.521T>C; rs4149056). Clinicians were presented with CDS when simvastatin was prescribed for patients with IF or PF through the electronic health record. Importantly, 64.2% of the CDS deployed at the point‐of‐care was accepted by the prescribers and resulted in prescription changes. Statin intensity was found to significantly influence prescriber adoption of the pharmacogenetic‐guided CDS, whereas patient gender or race, prescriber type, or pharmacogenetic training status did not significantly influence adoption. This study demonstrates that primary care providers readily adopt pharmacogenetic information to guide statin therapy for the majority of patients with preemptive genotype data.